2014
DOI: 10.1177/1528083714559568
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability analysis of nano-particulate-filled phenolic-based friction composite materials

Abstract: This research article reports the thermal stability behaviour of nano-particulates (multiwalled carbon nanotube and nanoclay)-filled Kevlar-lapinus fibre-reinforced phenolic resin-based friction composite under oxygen atmosphere using thermogravimetric analysis. To analyse the damage assessment of the proposed nano-particulates-filled composites under thermal surroundings, the thermograph of the composites are generally divided into three major temperature zones (i.e. zone-1, zone 2 and zone-3). Temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…After setting up examinations between carbon nanotubes and asbestos nanotubes, Murr and Soto revealed that the inclusion of carbon nanotubes to assess the tribo‐performance of friction composites in braking circumstance has turned into a conspicuous interest. Further, Hwang et al and Singh et al reported that addition of MWCNT and nanoclay in friction materials resulted in improved fade and recovery performances with higher label of COF. Liu et al investigated the tribo‐performance of nano rubber filled friction materials, finding that nanorubber inclusion improve the friction and wear performance.…”
Section: Introductionmentioning
confidence: 99%
“…After setting up examinations between carbon nanotubes and asbestos nanotubes, Murr and Soto revealed that the inclusion of carbon nanotubes to assess the tribo‐performance of friction composites in braking circumstance has turned into a conspicuous interest. Further, Hwang et al and Singh et al reported that addition of MWCNT and nanoclay in friction materials resulted in improved fade and recovery performances with higher label of COF. Liu et al investigated the tribo‐performance of nano rubber filled friction materials, finding that nanorubber inclusion improve the friction and wear performance.…”
Section: Introductionmentioning
confidence: 99%
“…The selected ingredients were weighted in an electronic weighing machine and mixed in a shear mixture for their proper distribution. Mixing schedule, sequence and fabrication details of the friction composites were reported elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…4 and 5). However, in case of LW0/LW-1/LW-2, the higher magnitude of friction coefficients may be attributed to the presence of hard lapinus fibre that enhances the abrasive component and aids the thermal resistance of the friction materials contributing to enhanced thermal stabilization (Singh et al, 2014). The increase in l R is due to disintegration of loosely compacted wear debris during the recovery cycle leading to the formation of third bodies between the pad and disc interface.…”
Section: Friction-evolution As a Function Of Braking Cyclesmentioning
confidence: 97%